Nitrile butadiene rubber-based heat-shielding insulations for solid rocket motors: Effect of polyimide fibrous reinforcement on the morphology and properties. (March 2015) - Zhao, Yuan; Hu, Shihao; Liu, Wei; An, Guangliang; Wu, Zhanpeng; Wu, Dezhen; Jin, Riguang
Chopped polyimide (PI) fiber-filled nitrile butadiene rubber (NBR) insulations for solid rocket motors were fabricated by surface modification of chopped PI fibers treated under oxygen plasma and subsequently by mixing formulation of NBR insulations on a two-roll mill. The effects of chopped PI fibers' surface modification on the mechanical and ablative properties were investigated. Results showed that excellent mechanical and ablative properties of the NBR insulations were attributable to the high thermal stability and unique interfacial interactions between fiber and the matrix because of the rougher surface character of modified chopped PI fibers. The microstructures of insulation and ablated charred layers were also characterized by scanning electron microscopy and atomic force microscopy.